ENHANCE SALES PERFORMANCE WITH FACEBOOK ADVERTISING IN SMES AGRIBUSINESS SECTOR - Norrahmiati (Universitas Lambung Mangkurat, 2020)
Nowadays, technology grows rapidly that makes the rate of adoption technology becomes high, especially in the field of marketing. Enhancement of the adoption technology from a marketing perspective prompt this research to focuses on the relationship between the utilization of social media Facebook as advertising with sales performance. Thus this study analyzes the factors that can influence when adopting Facebook as an advertising medium in the agribusiness sector SMEs and their impact on sales performance. This research focuses on SMEs in the East Java region of Indonesia. The research data was conducted quantitatively by giving questionnaires to SME owners. 102 valid data were received and analyzed using PLS analysis with the help of the SmartPLS 3.0 application. To examine the factors that can influence the adoption of SMEs to use Facebook ads, we use the TAM and DIT models, and we add other variables such as demographic targeting, interactivity and brand awareness. The results show that all of these factors have a significant influence on the use of Facebook ads. Next, we also analyze the impact of using Facebook ads on sales performance. The result shows that using Facebook ads as a marketing tool will improve SME sales performance.